Consider the symmetric, positive definite matrix $\mathbf{A}$. I'd like to find a general form for

$$(\mathbf{I} + \mathbf{A})^{-1}$$

that only involves $\mathbf{A}^{-1}$, i.e., no other inverse appears in the solution (as, for instance, in the Woodbury matrix identity).

I've tried to derive the inverse by hand but I could only obtain a result up to he $4 \times 4$ case as follows.

  • $2 \times 2$:

$$(\mathbf{I} + \mathbf{A})^{-1} = \frac{\mathrm{det}(\mathbf{A}) \mathbf{A}^{-1} + \mathbf{I}}{\mathrm{det}(\mathbf{A}) + \mathrm{tr}(\mathbf{A}) + 1}$$

  • $3 \times 3$:

$$(\mathbf{I} + \mathbf{A})^{-1} = \frac{\mathrm{det}(\mathbf{A}) \mathbf{A}^{-1} - \mathbf{A} + \big( \mathrm{tr}(\mathbf{A}) + 1 \big) \mathbf{I}}{\mathrm{det}(\mathbf{A}) + \mathrm{det}(\mathbf{A}) \mathrm{tr}(\mathbf{A}^{-1}) + \mathrm{tr}(\mathbf{A}) + 1}$$

  • $4 \times 4$:

$$(\mathbf{I} + \mathbf{A})^{-1} = \frac{\mathrm{det}(\mathbf{A}) \mathbf{A}^{-1} + \mathbf{A}^2 - \mathrm{tr}(\mathbf{A}) \mathbf{A} - \mathbf{A} + \big( \tfrac{1}{2}(\mathrm{tr}(\mathbf{A})^2-\mathrm{tr}(\mathbf{A}^2)) + \mathrm{tr}(\mathbf{A}) + 1 \big) \mathbf{I}}{\mathrm{det}(\mathbf{A}) + \tfrac{1}{2}(\mathrm{tr}(\mathbf{A})^2-\mathrm{tr}(\mathbf{A}^2)) + \mathrm{det}(\mathbf{A}) \mathrm{tr}(\mathbf{A}^{-1}) + \mathrm{tr}(\mathbf{A}) + 1}$$

Can we find a general expression for higher dimensions that builds on the ones above? Even obtaining the $5 \times 5$ case is prohibitive, and so far I haven't been able to spot the pattern.

  • $\begingroup$ I think the next case ($4\times 4$) is the crucial one. If you replace $A$ by $tA$ to keep track of the terms the middle term, the $t^2$ one of the denominator, is the trace of the matrix of $2\times 2$ cofactors, $\mathrm{tr}(A^{(2)})$ and I can't see how to get this in the form you want. $\endgroup$ – ancientmathematician Mar 7 '18 at 16:40
  • $\begingroup$ By the way I think that if you can do the case of $A$ diagonal you can do the general case by a change of basis. $\endgroup$ – ancientmathematician Mar 7 '18 at 16:41
  • $\begingroup$ Well, if $\mathbf{A}$ is diagonal, then the inverse is trivial. Can you please be more specific? $\endgroup$ – TheDon Mar 7 '18 at 23:41
  • $\begingroup$ It is trivial when $A$ is diagonal to write the inverse in terms of the eigenvalues, but the trick is to write it in terms of $A$ etc. This is not so easy. $\endgroup$ – ancientmathematician Mar 8 '18 at 7:47
  • 1
    $\begingroup$ I still think that if one can get the $4\times 4$ case then one will be able to spot the pattern. I do not have a computer algebra package to check, but I think the answer is something like $I + (\mathrm{tr}(A)I-A) +(\mathrm{tr}({A^{(2)})} I -\mathrm{tr}(A)A +A^2)+\mathrm{det}(A)A^{-1}$. $\endgroup$ – ancientmathematician Mar 8 '18 at 10:30

Let $p(x)=\sum_{k=0}^na_kx^k$ (with $a_n=1$) and $q(x)$ be the characteristic polynomials of $A$ and $B=I+A$ respectively. By Cayley-Hamilton theorem, $B^{-1}=g(B)$ where \begin{align} g(x) &=\frac{q(0)-q(x)}{xq(0)}\\ &= \frac{p(-1)-p(x-1)}{xp(-1)}\\ &=\frac{-\sum_{j=0}^n a_j[(x-1)^j - (-1)^j]}{xp(-1)}\\ &=\frac{-\sum_{j=1}^n a_j \sum_{k=0}^{j-1}(-1)^{j-1-k}(x-1)^k} {\sum_{j=0}^n (-1)^ja_j}\\ &=\frac{-\sum_{j=0}^{n-1} a_{j+1} \sum_{k=0}^j(-1)^{j-k}(x-1)^k}{\sum_{j=0}^n (-1)^ja_j}. \end{align} Therefore, $(I+A)^{-1}$ can be expressed in terms of $A$ by $f(A)$, where \begin{align} f(x) &=\frac{-\sum_{j=0}^{n-1} a_{j+1} \sum_{k=0}^j(-1)^{j-k}x^k} {\sum_{j=0}^n (-1)^ja_j}\\ &=\frac{-\sum_{k=0}^{n-1} x^k \sum_{j=k}^{n-1} (-1)^{j-k} a_{j+1}} {\sum_{j=0}^n (-1)^ja_j}\\ &=\frac{-\sum_{k=0}^{n-1} x^k \sum_{j=0}^{n-1-k} (-1)^j a_{j+k+1}} {\sum_{j=0}^n (-1)^ja_j}. \end{align} That is, $$ (I+A)^{-1}=\frac{-\sum_{k=0}^{n-1}\left[\sum_{j=0}^{n-1-k} (-1)^j a_{j+k+1}\right] A^k} {\sum_{j=0}^n (-1)^ja_j}.\tag{1} $$ It is well-known that each coefficient $a_i$ can be expressed in terms of the traces of the powers of $A$. More specifically, by Girard-Waring formula, if we define $s_k=\operatorname{tr}(A^k)$, then $$ a_{n-m} = \sum_{\substack{k_1+2k_2+\cdots+mk_m=m\\ k_1,k_2,\ldots,k_m\ge0}}(-1)^{k_1+k_2+\cdots+k_m}\frac{1}{k_1!k_2!\cdots k_m!}\left(\frac{s_1}1\right)^{k_1}\left(\frac{s_2}2\right)^{k_2}\cdots\left(\frac{s_m}m\right)^{k_m}.\tag{2} $$ In particular, when $n=5$, we have $a_5=1,\ a_0=-\det(A)$ and \begin{align} a_1 &=-\frac{s_4}4 + \frac{s_2^2}8 + \frac{s_1s_3}3 - \frac{s_1^2s_2}4 + \frac{s_1^4}{24},\\ a_2&= -\frac{s_3}3 + \frac{s_1s_2}2 - \frac{s_1^3}6,\\ a_3&= \frac{s_1^2-s_2}2,\\ a_4&= -s_1, \end{align} but surely, if $A^{-1}$ is also known, we would express $a_1$ as $\det(A)\operatorname{tr}(A^{-1})$ instead. Plug these into $(1)$, you can express $(I+A)^{-1}$ as a weighted sum of the powers of $A$ when $n=5$.

  • $\begingroup$ Thank you for your answer, this is closer to what I was looking for. Is there a way to simplify the expression of the coefficients $a$ if $\mathbf{A}^{-1}$ is known? For what I see, we have the following (for any $n$): $a_{n} = 1$, $a_{n-1} = - \mathrm{tr} (\mathbf{A})$, $a_{n-2} = \tfrac{1}{2} \big( (\mathrm{tr} (\mathbf{A}))^{2} - \mathrm{tr} (\mathbf{A}^{2}) \big)$, $\ldots$, $a_{1} = \mathrm{det} (\mathbf{A}) \mathrm{tr} (\mathbf{A}^{-1})$, $a_{0} = (-1)^{n} \mathrm{det} (\mathbf{A})$. $\endgroup$ – TheDon Mar 13 '18 at 16:22
  • $\begingroup$ @TheDon Not sure, but I don't think so. Note that $A^{-1}=\frac{-1}{a_0}\sum_{k=1}^na_kA^{k-1}$. If you subtract a multiple of $A^{-1}$ from $(1)$, there are still at least $n-1$ terms remain. So, you'll have a sum of $n$ terms anyway. $\endgroup$ – user1551 Mar 13 '18 at 17:15
  • $\begingroup$ Do you have any answer to this?: math.stackexchange.com/questions/3184171/… $\endgroup$ – Susan_Math123 Apr 11 '19 at 19:51

Let $A\in M_n(\mathbb{C})$, $spectrum(A)=(\lambda_i)$ and $B=I+A$ (we assume that $-1\notin spectrum(A)$); note that $spectrum(B)=(1+\lambda_i)$.

Proposition. $(I+A)^{-1}$ is a polynomial of degree $n-1$ in $A$, the coefficients of which, are rational functions of the $(trace(A^k))_{k\leq n}$.

Proof (for $n=5$). Let $(\sigma_k)$ be the elementary symmetric functions of the $(\lambda_i)$ and $(\tau_k)$ be the elementary symmetric functions of the $(1+\lambda_i)$. According to Hamilton-Cayley:


Each $B^k$ is a polynomial of degree $k$ in $A$.

On the other hand, each $\tau_k$ is a symmetric function of the $(\lambda_i)$, then a polynomial in $\sigma_1,\cdots,\sigma_k$. Since each $\sigma_k$ is a polynomial in $trace(A),\cdots,trace(A^k)$ (use the Newton's formulae), $\tau_k$ is a polynomial in $trace(A),\cdots,trace(A^k)$.

Finally, $(I+A)^{-1}$ is a polynomial in $A$, the coefficients of which, are rational functions of the $(trace(A^k))_{k\leq 5}$.

Remark. Of course, we may replace the characteristic polynomial of $A$ with its minimal polynomial.

EDIT. Answer to @ancientmathematician ; cf. below a procedure (in Maple) that works for every dimension $m$ (I use the Bell function).

***Decomposition of $(I+A)^{-1}$; the result is in "res"; $a$ denotes $A\in M_m$ and $t[i]=t_i$ denotes $Trace(A^i)$.




TAU:=Vector(m): for n from 1 to m do U:=Matrix(n,n): for i to n-1 do U[i+1, i] := -1 end do; S := Vector(n, symbol = s); X := Vector(n, symbol = x); for i to n do x[i] := -factorial(i-1)*s[i] end do;

for i to n-1 do for k to i do U[i+1-k, i] := x[k]*binomial(n-i-1+k, k-1) end do end do;

for i to n do U[i, n] := x[n-i+1] end do;

TAU[n] := (-1)^n*Determinant(U)/factorial(n);


for k from 1 to n do

rr:= (1+y)^(k): ss:=m:

for i from 1 to k do ss:=ss+coeff(rr,y,i)*t[i]: od: s[k]:=ss: od:

TAU[n]:=expand(TAU[n]): x:='x':s:='s':t:='t': od: ;

***$(I+A)^{-1}$ as a polynomial in $A$

res := (1+a)^(m-1);

for i from m-2 by -1 to 0 do res := res+(-1)^(i-m+1)TAU[m-i-1](1+a)^i end do;

res := (-1)^(m-1)*collect(expand(res), a)/TAU[m];


A := RandomMatrix(m,m);

B := 1/(IdentityMatrix(m)+A);

a := A; for i to m do t[i] := Trace(A^i) end do;


  • 1
    $\begingroup$ I agree with all this. But I am left with a nagging doubt about whether the final answer simplifies to something more recognisable. After all we've got the expansion of powers of $(I+A)$; the replacement of the $\tau_j$ by expressions in the $\sigma_j$ [which can also be expressed as $\chi_{A+I}(x)=\chi_{A}(x-1)$]; and the replacement of the elementary symmetric functions by the powers sum ones. $\endgroup$ – ancientmathematician Mar 10 '18 at 12:13
  • $\begingroup$ Thanks for your answer. Can you please clarify if there is a closed-form expression for the coefficients $\tau_{k}$? $\endgroup$ – TheDon Mar 12 '18 at 10:10
  • $\begingroup$ Of course, no. I wrote the above procedure to show to @ancientmathematician (now he disappeared...) that the method works. In particular, for $n=10$ the time of calculation is $0"5$ but the result fills 2.5 Maple sheets. $\endgroup$ – user91684 Mar 12 '18 at 23:04
  • $\begingroup$ @loupblanc, I have no doubt the method works, I was about to post an account of it, but you beat me to it! But I am still not convinced there is not a way to express the answer in terms of the theory of symmetric functions. $\endgroup$ – ancientmathematician Mar 13 '18 at 7:52
  • $\begingroup$ Do you have any answer to this?: math.stackexchange.com/questions/3184171/… $\endgroup$ – Susan_Math123 Apr 11 '19 at 19:52

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.